An adventurous learning journey. Physiotherapists’ conceptions of learning and integrating cognitive functional therapy into clinical practice - Holopainen, Riikka; Piirainen, Arja; Karppinen, Jaro; Linton, Steven James; O’Sullivan, Peter (Physiotherapy theory and practice, 2022)
: Recent low back pain guidelines recommend a BPS approach to the management of disabling low back pain. However, the most effective way of teaching physiotherapists to implement these approaches remains unknown. The present qualitative study aimed to explore physiotherapists' conceptions of learning and integrating Cognitive Functional Therapy (CFT) into clinical practice in Finnish primary health care. : We interviewed 22 physiotherapists, who participated in four to six days of CFT workshops. A phenomenographic approach was used to explore the variation in the physiotherapists' conceptions of this process. : Four themes emerged from the data: 1) membership of work community; 2) learning journey; 3) transition to new working methods; and 4) professional role as a physiotherapist. These themes varied in four categories of description: recognizing difference of the new approach, toward integrating the new approach, waking up to explore, commitment to new approach and expanding application of new approach. The critical aspects between the categories that enabled the integration of CFT into clinical practice were ability to overcome resistance and to change views, being shaken and ability to critically reflect on one's work, support from the work community and becoming convinced, creativity, multidisciplinary collaboration and continuous learning. : The participants' responses to the training varied greatly, suggesting that for some, the training was insufficient to support adequate changes in their practice behavior; whereas for others, the training was a life changing experience.